Qarar in International Oil and Gas Contract - Mohammad hossein Esfandiarpour; Ahmad Shaabani (تحقیقات مالی اسلامی (پیوسته))
International Petroleum Contracts (IPCs) has been made between Host Countries (HCs) and International Oil Companies (IOCs). By this kind of contracts, IOCs provide financial resources, technology and management necessary for oil and gas fields’ development and benefit from the produced oil and gas. Needlaess to say, due to various and broad operations, unpredictable increase and decrease in market prices, unforeseeable rservoire behavior, and in one word, Because of major technical and financial risks, there is a great uncertainty in both sides of the contract, the amount and conditions of investment and outcomes. From the Islamic jurisprudence viewpoint, those risks would cause “Qarar” and affect the validity of contract. For reviewing abovementioned hypothesis, first, the precedent studies has been examined and the consequent is only those uncertainties that may lead to dispute from commom sense view would enter “Qarar” into the contract. After that, this measuremen is applied to the IPC’s contents. At the end, it is concluded that it is not necessary for parties to know every aspect of the contract and its outcome in full and they could put the contract out of the “Qarar” area by implementing risk management tools such as price formulas, Adjustment terms and industrial standards. In other word, according to the oil and gas professionals’ course of conduct such risks could be waived and consequently, the common risks of these contracts can not affct their validity totally.